Culture and Mentality-Related Specifics of Implementation of the ‘Law on Counteracting Bullying’ in the Environment of Educational Institutions - BOCHELIUK, Vitalii I.; NECHYPORENKO, Valentyna V.; POZDNIAKOVA, Olena L.; SILIAVINA, Yuliia S.; KYRBIATIEV, Oleg O. (Journal of Advanced Research in Law and Economics, 2020)
Abstract : The article sought to analyse the pedagogical instruments capable to bring change in culture and mentality-based perception of bullying among stakeholders of the educational process with the purpose of implementation of the Law ‘On Amendments to Certain Legislative Acts of Ukraine on Counteracting Bullying (Harassment)’ in the environment of educational institutions. This study used theoretical methods: analysis of scientific, pedagogical and regulatory sources in order to distinguish the gaps and areas to study in this particular problem, analysis of domestic and foreign best practices; empirical methods: diagnostic: survey questionnaires; statistical methods: quantitative analysis of the results of the survey questionnaires. The statistical data the authors obtained as a result of a survey of students from four schools prove that the problem of bullying in Ukrainian educational institutions is partially caused by socio-cultural and mental impact factors. Examples of overseas best practices in addressing the problem of bullying prevention in educational institutions, which can be adapted to the realities of Ukrainian educational institutions, include further outlined role-pays: ‘School Anti-Bullying Court’ and ‘Shuttle Diplomacy’ and the ‘Student Support Service’ model. Bullying is, to a large extent, a socio-cultural and mental problem of Ukrainian society, capable of dramatically affecting students’ learning abilities and their socialisation. Pedagogical tools to be used to deal with the above problem might be (a) regular anonymous interviewing of students about cases of violence; (b) teachers' educational work with children and parents on the problem of bullying; (c) involvement of the students in the development of rules of conduct; (d) teachers supervising schoolchildren after school hours; (e) teacher training (professional upgrade) for pedagogical, psychological and legal strategies for bullying prevention among students.